The Effectiveness of Implementing Law Number 23 of 2004 on Elimination of Violence in Household: Case Study in Makassar City - A. Dewi Vitasari; Hambali Thalib; Sufirman Rahman (Sovereign: International Journal of Law, 2020)
This study aims to determine the effectiveness of implementing Law Number 23 of 2004 on Elimination of Violence in Household, as well as the factors that influence its enforcement. This type of research is empirical legal research with a quantitative descriptive in nature. This research was conducted in Makassar City to be precise at the Makassar City Police. The data collection techniques used in this study were questionnaires, documentation, and literature study. The data analysis technique used is quantitative data analysis techniques. The results showed that the implementation of Law No. 23 of 2004 in Makassar City is still considered less effective. Factors affecting the effectiveness of the implementation of Law No. 23 of 2004 in Makassar City consists of several factors, namely: legal factors; law enforcement factors; supporting facility factors; environmental factors; and cultural factors. in addition, environmental factors are the biggest factor affecting the effectiveness of the implementation of Law No. 23 of 2004. It is hoped that the police will further strengthen environmental factors in order to increase the effectiveness of the implementation of Law No. 23 of 2004 in the future.